Triumph of the City: How Our Greatest Invention Makes Us Richer, Smarter, Greener, Healthier, and Happier (an excerpt) (translated by Innа Kushnareva) - GlaeserEdward L. (Journal of Economic Sociology, 2013)
Why do more than half the world’s population prefer to live in cities? Why do the richest and poorest people in the world so often live cheek by jowl? How do once-mighty cities fall into disrepair? Why are only some of them capable of recovering and making a comeback? In his book «Triumph of the City: How Our Greatest Invention Makes Us Richer, Smarter, Greener, Healthier, and Happier», Glaeser proposes answers to these issues and many others. The journal «Economic Sociology» publishes the conclusion of this book «Flat World, Tall City».